Communication Strategies in Delivering Educational Messages on Song Lyrics “Lamunan” and “Lestari” - Eka Butsiawan; Roekhan Roekhan; Kusubakti Andajani (PT. Anagata Sembagi Education, 2024)
This research focuses on two songs by Wahyu F. Giri,